Peripapillary retinal nerve fiber layer and ganglion cell complex in Alzheimer’s disease - R.N. Gulieva (РМЖ "Клиническая офтальмология")
R.N. Gulieva A.I. Karaev Institute of Physiology of Azerbaijan National Academy of Sciences, Baku, Azerbaijan Aim: to measure retinal nerve fiber layer (RNFL) thickness and ganglion cell complex (GCC) thickness in patients with Alzheimer’s disease (AD). Patients and Methods: 45 patients (88 eyes) aged 58–74 years (mean age 66.2±3.44 years) with AD and mild cognitive impairment (10 men and 35 women) were examined. Inclusion criteria were normal IOP levels and the ability to understand the aim of the study. Exclusion criteria were ametropia greater than 5 diopters or axial length more than 25 mm, severe dementia, cerebrovascular disorders, metabolic and mental disorders, glaucoma, uveitis, retinal diseases, diabetes, and anamnestic stroke. Controls were 60 patients (115 eyes) without AD (mean age 59.6±2.03 years, 17 men and 43 women). Standard eye examinations and optical coherence tomography were performed, cognitive functioning was assessed. Results: in AD patients, average, temporal, nasal superior, and inferior RNFL thickness was less by 27.0%, 15.4%, 17.9%, and 24.9%, respectively, as compared with controls. Mean, superior, and inferior GCC thickness was reduced while focal loss volume and global loss volume were greater by 1.7 times (p<0.05) and 2.8 times (p<0.01), respectively, as compared with controls. Conclusions: temporal, superior, and inferior RNFL thickness is significantly reduced in AD patients (p<0.001). All GCC parameters are changed as well, i.e., average, inferior, and superior GCC thickness is reduced while focal loss volume and global loss volume are significantly increased (p<0.01). Keywords: Alzheimer’s disease, optical coherence tomography, retina, nerve fibers, ganglion cell complex, thickness, quadrant. For citation: Gulieva R.N. Peripapillary retinal nerve fiber layer and ganglion cell complex in Alzheimer’s disease. Russian Journal of Clinical Ophthalmology. 2020;20(2):63–66. DOI: 10.32364/2311-7729-2020-20-2-63-66.